European consensus on patient contact shielding. (April 2022) - Hiles, Peter; Gilligan, Patrick; Damilakis, John; Briers, Eric; Candela-Juan, Cristian; Faj, Dario; Foley, Shane; Frija, Guy; Granata, Claudio; de las Heras Gala, Hugo; Pauwels, Ruben; Sans Merce, Marta; et al.
Highlights: Shielding use in radiology has been re-evaluated. Major European bodies involved in imaging radiation safety have issued consensus based recommendations. This paper represents multidisciplinary based recommendations for shielding use. In the majority of cases patient contact shielding use is not recommended. Abstract: Patient contact shielding has been in use for many years in radiology departments in order to reduce the effects and risks of ionising radiation on certain organs. New technologies in projection imaging and CT scanning such as digital receptors and automatic exposure control (AEC) systems have reduced doses and improved image consistency. These changes and a greater understanding of both the benefits and the risks from the use of shielding have led to a review of shielding use in radiology. A number of professional bodies have already issued guidance in this regard. This paper represents the current consensus view of the main bodies involved in radiation safety and imaging in Europe: European Federation of Organisations for Medical Physics, European Federation of Radiographer Societies, European Society of Radiology, European Society of Paediatric Radiology, EuroSafe Imaging, European Radiation Dosimetry Group (EURADOS), and European Academy of DentoMaxilloFacial Radiology (EADMFR). It is based on the expert recommendations of the Gonad and Patient Shielding (GAPS) Group formed with the purpose of developing consensus in this area. The recommendations are intended to be clear and easy to use. They are intended as guidance, and they are developed using a multidisciplinary team approach. It is recognised that regulations, custom and practice vary widely on the use of patient shielding in Europe and it is hoped that these recommendations will inform a change management program that will benefit patients and staff.